Participatory social network map making with family carers of people living with dementia. Issue 1 (April 2019) - Campbell, Sarah; Clark, Andrew; Keady, John; Kullberg, Agneta; Manji, Kainde; Rummery, Kirstein; Ward, Richard
This article focuses on the use of a participatory social network mapping method with family carers. This is one of a suite of methods developed in a 5-year qualitative multi-centre project exploring how neighbourhoods support, enable or disable people with dementia and their families to live well in their communities. The article considers how mapping provides insights into family support networks, revealing the fluidity of support and care within relationships as well as providing opportunity for individuals to represent the complexities of their relationships with more and less significant others. However, the potential offered by the approach goes beyond those of visual representations of networks and contacts. Paying attention to the co-production process, as well as the reflexive dialogue that emerges in the exchange between researcher, participants, and the maps themselves, we consider how the maps emerge as affective artifacts, weighted with emotion.